Economic Growth and Foreign Direct Investment Inflows: The Case of Qatar - Almfraji, Mohammad Amin; Almsafir, Mahmoud Khalid; Liu, Yao (Elsevier, 2014)
Recently, Qatar, a well-known oil production country, has been convinced as a successful case in attracting foreign direct investment (FDI) as a smaller economy. This paper aims to investigate how FDI inflows affect Qatar’s business cycles. Time-series data was selected from 1990 to 2010 as available. The VAR Impulse Responses and the Granger Causality test were mainly employed by using Eviews. The derived result shows that the FDI inflows and the economic growth in Qatar interact with each other in a relatively long term.